2006
DOI: 10.1016/j.pain.2006.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Fear-avoidance beliefs about back pain in patients with subacute low back pain

Abstract: The fear-avoidance beliefs of patients with subacute low back pain (LBP) considered at risk for chronic disabling LBP are not well known. The objectives of this cross-sectional descriptive survey, conducted in secondary care practice, were to assess fear-avoidance beliefs about back pain in patients with subacute LBP and to seek an association between physician or patient characteristics and level of fear-avoidance beliefs. A total of 286 rheumatologists completed a self-administered questionnaire assessing ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
9
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 24 publications
4
46
9
5
Order By: Relevance
“…or chronic LBP patients in previous French studies (23,(28)(29)(30)(31)(32). Thus, the population of our study is likely to be a mix of pain-free workers (as expected) with other workers suffering from "highly recurrent" LBP.…”
Section: Chaléat-valayer Et Almentioning
confidence: 78%
“…or chronic LBP patients in previous French studies (23,(28)(29)(30)(31)(32). Thus, the population of our study is likely to be a mix of pain-free workers (as expected) with other workers suffering from "highly recurrent" LBP.…”
Section: Chaléat-valayer Et Almentioning
confidence: 78%
“…Our participants had all consulted for low back pain in the previous 6 months and had significant ongoing problems. They might, however, not be the same population as those currently attending for treatment who will tend to have more severe symptoms (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Klaber-Moffett et al [23] recommended a cut-off score [ 13 based on a median split of baseline scores, and found that patients with chronic LBP scoring above this cut-off were more likely to benefit from an exercise program instead of usual care. Poiraudeau and colleagues [34] found that patients with sub-acute LBP scoring above this threshold had higher levels of disability and anxiety.…”
Section: Introductionmentioning
confidence: 97%